Correspondence from Honey Toda to Betty Salzman, July 26, 1942 - Honey Toda::::::author
Personal letter mentions mutuel acquaintances and desire to see visitors, a ban on anything other than business visitors, and a requirement that all visitors must apply for permits. The letter also mentions the prospect of being in Manzanar for a long time. Toda states that camp life will not stop them from having fun, such as a picnics; she mentions "weiner bakes" along with hot, dusty conditions. She also notes Salzman's work on swing shifts and urges Salzman not to let her work get her down, but rather to "do your part for the U.S.A. - 'Keep them flying!'"